The Effect of Work-Family Conflict and Job Satisfaction on Organizational Commitment and Their Impact on the Turnover Intention of the Crew Of PT. Tanto Intim Line Jakarta - Ronaldo Tri Nova Caesa; Imam Sonny; Zaenal Abidin (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
Work-family conflict and job satisfaction are one of the factors that influence organizational commitment which can have an impact on the turnover intention of a worker, especially crew members. This study aims to determine whether there is an effect of work-family conflict and job satisfaction through organizational commitment and the desire to get in and out of the ship PT Tanto Intim Line Jakarta. This study used a sample of 494 ship respondents and the PLS SEM analysis method. The results of the study found that there was a negative influence on work-family conflict on organizational commitment where if work-family conflict was high, organizational commitment would be lower, and vice versa. In addition to job satisfaction has a positive effect on organizational commitment, organizational commitment also has a significant effect on turnover intention. It was also found that the mediating effect of organizational commitment on work family conflict and job satisfaction on turnover intention showed a negative mediating effect. Where the work family conflict variable increases, it can reduce organizational commitment so that the desire or desire to change companies is higher. Meanwhile, the increased job satisfaction variable can increase organizational commitment which has an effect on reducing turnover intention.